Hubungan Pengembangan Bahan Ajar dan Media Pembelajaran dengan Hasil Belajar Siswa pada Mata Pelajaran PAI di Sekolah Dasar - Achmad, Andi (SYAMIL, 2017)
The background of this research with low level of knowledge and understanding of students in the subjects taught in the educational unit. it is caused by a large load of the subjects taught, the number of core competencies and basic competencies are mastered, the lack of teaching materials used reference and instructional media use is considered monotonous. Therefore, the education unit is expected to have a strategy to deal with the issues involved, so that the learning process in educational units to run well so that student learning outcomes can be achieved to the fullest. One of them is the development of teaching materials and media learning. The purpose of this study to determine the relationship of the development of teaching materials and media with the results of student learning in Public Elementary Schools District Sungai Kunjang. This research is a quantitative study with associative approach. The number of respondents in this research is 160 students, this selection using quota sampling technique and proportional random sampling. The technique of data analysis in this research is using correlation test and t-test. The results of this research is there is a positive and significant relationship between the development of teaching materials and media with the results of student learning in Islamic Religious Education in Public Elementary Schools District Sungai Kunjang.